Analysis of The Implementation of The Double Track Program in Improving Entrepreneurial Interests of Grade XI Students at SMAN 1 Berbek - Milasari, Vika Sintya; Suswanti Respatiningtias, Dyah; Bawono, Muhammad; Arintowati, Dyan (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study aims to test the influence of the Double Track Culinary Arts and Double Track Make-up Programs on increasing the interest in entrepreneurship of class XI students at SMAN 1 Berbek. Method: This study's population consisted of 60 Double-Track participants. The saturated sampling technique was used for sampling. The data collection methods used were observation and questionnaires, and the data analysis technique used was multiple linear regression. Research Finding: The study's results show that the Double Track Culinary Arts and Double Track Make-up Arts variables have a positive effect on increasing the interest in entrepreneurship of class XI students at SMAN 1 Berbek. Originality: This research provides a more detailed picture of the Double Track program's influence on increasing students' interest in entrepreneurship.